Functional electrical stimulation for foot drop in people with multiple sclerosis: The relevance and importance of addressing quality of movement - Smith, Angela Davies; Prokopiusova, Terezie; Jones, Rosemary; Burge, Tania; Rasova, Kamila (Multiple sclerosis, 2021)
Impaired mobility is common in people with multiple sclerosis (MS). Changes in gait have different causes and require individualised gait rehabilitation. A common and often early cause of mobility impairment is footdrop, inability to lift the foot during the swing phase of gait, with increased risk of falls, effortful walking and fatigue. Using literature review, we have characterised published data on footdrop treatment in MS, specifically functional electrical stimulation (FES) to better understand the reported outcomes relevant to the user. We discuss the strengths and weaknesses of FES and how far it meets the needs of people with footdrop. Physiotherapy combined with FES may further enhance the benefits of FES. MS studies emphasise the value of maintaining activity levels in early MS but discussion on how to achieve this is lacking. We emphasise the value of qualitative measures to broaden our understanding and improve treatment and adherence and identify areas for further research. Supplementary video material illustrates key features of MS gait and its correction using FES and physiotherapy.
Keywords: neuropatie nervus peroneus; Gait; Electric Stimulation; Electric Stimulation Therapy; Peroneal Neuropathies; chůze (způsob); elektrická stimulace; Humans; roztroušená skleróza; lidé; Multiple Sclerosis; elektrostimulační terapie